1990
DOI: 10.1149/1.2086439
|View full text |Cite
|
Sign up to set email alerts
|

The Early Stage of Atmospheric Corrosion of Copper by Sulfur Dioxide

Abstract: The early stage of corrosion of copper by moist air containing 0.5% sulfur dioxide (75% relative humidity at 25~ has been studied. Scanning electron microscopy, Auger electron spectroscopy, and transmission electron microscopy have been used to examine the surface topography, surface chemistry, and microstructure of copper foils before and after exposure to the corrosive atmosphere. The analyses show that in the initial stage of corrosion a mixture of copper oxide and copper sulfide forms on the surface. Reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
3

Year Published

1990
1990
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 11 publications
0
18
0
3
Order By: Relevance
“…Later the typical greenish color of the copper patina appears. The primary corrosion product present at that time is posnjakite, Cu 4 (SO 4 )(OH) 6 •H 2 O, which later converts to brochantite, Cu 4 (SO 4 )(OH) 6 . Additionally smaller amounts of antlerite, Cu 3 (SO 4 )(OH) 4 , atacamite, Cu 2 Cl(OH) 3 , and organic components were found.…”
mentioning
confidence: 99%
“…Later the typical greenish color of the copper patina appears. The primary corrosion product present at that time is posnjakite, Cu 4 (SO 4 )(OH) 6 •H 2 O, which later converts to brochantite, Cu 4 (SO 4 )(OH) 6 . Additionally smaller amounts of antlerite, Cu 3 (SO 4 )(OH) 4 , atacamite, Cu 2 Cl(OH) 3 , and organic components were found.…”
mentioning
confidence: 99%
“…For copper, the bisulfite seen in the S 2p XPS spectra originated from SO 2 adsorption on the surface electrolyte, as shown in equation (1). Although Chawla and Payer reported the formation of copper sulfide (Cu 2 S) in the early stage of copper corrosion with 0.5 SO 2 , 28) we did not detect any sulfide component (Fig. 9(b)).…”
Section: )mentioning
confidence: 68%
“…Chawla et al reported that they found cuprite in the ED pattern of an unexposed copper surface. 20 The oxide thickness is several nanometers and its existence can be confirmed by XPS. The O 1s XPS spectra of as-cleaned copper included the lattice oxygen component ͑O 2Ϫ in Cu 2 O͒.…”
Section: Resultsmentioning
confidence: 86%
“…Figure 3 shows a ternary Cu-S-O compositional triangle. 20 The compositions of the crystallized and noncrystallized phases are plotted as an open circle A and a closed circle B, respectively. The composition of the crystallized phase was very close to the theoretical composition of antlerite also shown in Fig.…”
Section: Resultsmentioning
confidence: 99%